Letter to the Editor on: “Effectiveness of Multi-activity, High-intensity Interval Training in School-aged Children.” - Mans, M.F.T.; van der Most, F.; Cloosterman, K.L.A. (International Journal of Sports Medicine, 2021)
Recently, Ketelhut et al. published an article on the effectiveness of a multi-activity high-intensity interval training in school-aged children on aerobic fitness and hemodynamic parameters in the International Journal of Sports Medicine. With this letter to the editor we would like to comment on the methods and clinical relevance of the results found.